Rancang Bangun Modul Aplikasi Link Budget Coverage Area Berbasis Smartphone - Ahmad Nur Siswanto (Jurnal Jaringan Telekomunikasi, 2016)
Coverage is needed to determine the amount of signal coverage that can be reached by the antenna at the base station. Therefore, in order to know the coverage area of ??a base station, a link budget coverage area application is needed. The purpose of making a link budget coverage area calculation application system at a base station is to assist in calculating the link budget to determine the coverage area of ??a base station and is also used as a learning module for mobile communication systems at State Polytechnic of Malang. The method of determining the coverage area is done in 2 ways, namely the calculation using the application and the drive test. The method of calculating the link budget coverage area used is 3 models, the Okumura-Hatta model is used to calculate the GSM system coverage area, the Cost-231 Hatta model for the DCS system, and the Walfisch Ikegami model for the UMTS 2100 system. measurement of the signal level around the base station area. The comparison of the coverage area between the measurement and calculation results is almost close to the difference in coverage of less than 100 m. Wherefrom the results of the drive test, the farthest range is 980 m with a signal level value of -91 dBm. Meanwhile, from the calculation side, the results obtained coverage of 1.06 km and 1.05 km with a signal level of -90 dBm